Zinc protoporphyrin IX predominantly exists as a complex non-enzymatically bound to apo-hemoglobin in Parma ham. (30th November 2022) - Zhai, Yang; Wang, Hung-Cheng; Hayakawa, Toru; Kumura, Haruto; Wakamatsu, Jun-ichi
Highlights: Optimized experimental model significantly increases water-soluble ZnPP complexes. Easier hemoglobin heme release as substrate for ZnPP formation than from myoglobin. The iron ion released from heme was considered as a crucial ZnPP formation pathway. ZnPP-Hb was formed by binding ZnPP with apo-Hb non-enzymatically. Abstract: Most of the water-soluble zinc protoporphyrin IX (ZnPP) in Parma ham mainly exists as complexes with hemoglobin and myoglobin (ZnPP-Hb and ZnPP-Mb). To elucidate the formation mechanism of these complexes, a new experimental model to produce higher amount of water-soluble ZnPP complexes was established. ZnPP-Hb was detected as the main water-soluble ZnPP complex in this model, which is the same as that in Parma ham. Adding exogenous Hb into this model promoted higher ZnPP formation than with Mb added, indicating that Hb was the superior substrate for generating ZnPP compared to Mb. The increase in non-heme iron content with ZnPP formation in both the Hb- and Mb-added groups indicated that the release of iron ion from heme was a crucial step in ZnPP formation. ZnPP-Hb was formed when ZnPP non-enzymatically bound with apo-Hb. These results revealed the mechanism of why ZnPP-Hb is more dominant in Parma ham than to ZnPP-Mb.